USING VIRAL MARKETING THROUGH SOCIAL NETWORKS: A STATISTICAL STUDY - Hassen, Waleed A.; Shyaa, Methaq A.; Ibrahim, Hassan M. (International Journal of Psychosocial Rehabilitation, 2020)
Viral marketing is a type of marketing that spreads message of communication from one person to another like a virus. Theobjectives of this paper are: 1) achieve a research study on the impact of viral marketing on the desire of consumers in a number of social networking sites such as Facebook, YouTube, and Instagram; 2) perform a statistical analysis on these social networking sites to determine the most commonly used web site by our research sample; 3) determine the most important topics that the research sample cares about when using social media.To achieve the goals of this paper, the employed sample included 200 users from academic community in different specialties and faculties, those usually use social networks sites such as Facebook, YouTube, and Instagram. A survey paper was distributed to the research sample which contains a set of questions in order to achieve the goals presented above.The results showed that Facebook comes primarily as an important toolof viral marketingfollowed by YouTube and then Instagram. Furthermore, we found that the media materials supported by videos and images are more affect the wishes of consumers compared to other advertisements. Finally, there was a significant impact of viral marketing on the wishes of the consumers when they use social media.